Faktor-faktor yang Memengaruhi Kepuasan Konsumen dan Loyalitas Konsumen Beras BULOG di Kota Pangkalpinang - Karsiningsih, Eni; Armadini, Gianitasyah; Puwarsih, Rati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to determine the effect of product quality, price and product health on consumer satisfaction and consumer loyalty of BULOG rice in Pangkalpinang City. The time and place of this research was conducted from August 2023 to September 2023 in Pangkalpinang City. The research method used is the survey method. While the sampling method used is purposive sampling with a sample size of 100 respondents. Data analysis using SEM-PLS (Structural Equation Modelling-Partial Least Square) analysis with SmartPLS Version 4.0 software. The results showed that product quality and price directly have a significant effect on the satisfaction and loyalty of consumers who consumer BULOG rice. Consumer satisfaction has a significant effect on consumer loyalty. Meanwhile, product health has no significant effect on customer satisfaction. The results of indirect research on rice prices have a significant effect on loyalty through customer satisfaction, while product quality and product health have no significant effect on loyalty through customer satisfaction.